SOCIOECONOMIC CONDITION AND LAND USE TRANSFORMATION OF FARMERS IN MAIZE FARMING: THE CASE STUDY OF NAN PROVINCE, THAILAND - Pampasit, Rudklaw; Pampasit, Savent (PEOPLE: International Journal of Social Sciences, 2018)
This paper presents about socioeconomic condition and land use transformation of farmers in maize farming at Nan. Located in the northern region of Thailand, Nan is a province with limited arable areas. Since more than 87 percent of its landscape covers with mountainous forest and slope, the areas suitable for growing plants is barely 12 percent. The past 10 years thus have witnessed the increase of maize farming by forest encroachment. In contrast to the positive growth in quantity and price of maize, the poverty of Nan people however is getting worse. This is clearly evident in the rank of the poor across the Thai nation, while in 2004 Nan ranked number 39 but in 2011 its poor population ratio rose to number 21 of the country. Thus the key issues needed to be addressed by the government include the farmers’ socioeconomic condition, the constraint of land use in the slope areas, and the introduction of alternative plants for sustainable income and career.The researcher formulates the conceptual model that tries to infer about socioeconomic condition and land use transformation from field survey that includes 703 samples of farmers by questionnaires. This study found that the most influential factors affecting the decision to shift from growing maize to alternative plants were the market and the middleman, and the cost for growing alternative plants. However, the least influential factor was the knowledge in cultivating the alternative plants. In sum, the change in maize growing behavior was a result of price, income, and market factors.